Treatment of adult Valcheta frogs Pleurodema somuncurense for chytrid fungus - Arellano, Maria Luz (2018)
SUMMARY: Treatment of an ex-situ colony of Valcheta frog with chloramphenicol solution was not successful in eliminating chytrid fungus.